Rancang Bangun Prototype Pengaksesan Gudang Menggunakan Sistem Pengenalan Wajah - Huda, Nur; Bastian, Alvian; Ahyar, Muh. (KOMPUTEK, 2024)
In the era of globalization, technology is developing rapidly and has become an important aspect in improving security. Traditional security systems such as keys and access cards have several disadvantages, such as the risk of loss and misuse. To overcome this, this research designed and built a prototype warehouse access system using facial recognition technology based on ESP32-CAM and Firebase as a real-time database. This system aims to increase security and efficiency in managing warehouse access. The facial recognition system uses the Haar cascade classifier algorithm to detect and recognize the user's face, with an ESP32-based control module integrated with the camera, keypad and LCD screen. System testing involves variables such as facial expressions, accessories, lighting, and distance to ensure optimal performance in a variety of conditions. Apart from facial recognition, the system is also equipped with an alternative method of access using a PIN as a backup. Test results show that the system works well in various scenarios, with the level of usability assessed using the System Usability Scale (SUS) reaching a score of 76.7, which indicates a good level of usability. It is hoped that this system can be implemented to improve the security and efficiency of warehouse access in the future.